2017
DOI: 10.1364/boe.8.004310
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic tethers connect sister chromosomes and transmit “cross-polar” force during anaphase A of mitosis in PtK2 cells

Abstract: Originally described in crane-fly spermatocytes, tethers physically link and transmit force between the ends of separating chromosomes. Optical tweezers and laser scissors were used to sever the tether between chromosomes, create chromosome fragments attached to the tether which move toward the opposite pole, and to trap the tethered fragments. Laser microsurgery in the intracellular space between separating telomeres reduced chromosome strain in half of tested chromosome pairs. When the telomere-containing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…These results demonstrate that these structures likely play a role in coordinated chromosome movements in general, and must be considered in models of mitosis and meiosis (Forer et al, 2017). Furthermore, using optical tweezers, it was possible to calibrate the tethering force at 1.5 pN (Ono et al, 2017). Using optical tweezers to measure the force exerted on chromosomes is discussed below.…”
Section: Scissors Ii: Chromosome Movement In Mitosis/meiosismentioning
confidence: 96%
See 1 more Smart Citation
“…These results demonstrate that these structures likely play a role in coordinated chromosome movements in general, and must be considered in models of mitosis and meiosis (Forer et al, 2017). Furthermore, using optical tweezers, it was possible to calibrate the tethering force at 1.5 pN (Ono et al, 2017). Using optical tweezers to measure the force exerted on chromosomes is discussed below.…”
Section: Scissors Ii: Chromosome Movement In Mitosis/meiosismentioning
confidence: 96%
“…Another study combined laser scissors and tweezers to study the mechanical forces during mitosis (Ono et al, 2017). Optical tweezers and laser scissors were used to sever the tether between chromosomes, using the scissors to create chromosome fragments attached to the tether which move toward the opposite pole, and using the trap to stop the movements of the tethered fragments.…”
Section: Tweezers and Scissorsmentioning
confidence: 99%
“…104,105 When optical tweezers were used to trap a fragment tip that was created with laser scissors, the force that the tethers imparted on its partner was found to be ∼1.5 pN. 79 The function of the tethers is not completely understood. However, it has been shown that when kinetochore microtubules and tethers were cut during anaphase, the chromosome movements to the respective poles sped up, suggesting that the tethers may act to regulate the speed of chromosome movement.…”
Section: Optical Tweezersmentioning
confidence: 99%
“…Tethers occur between the tips of sister chromosomes and functional assays of the tethers consist of using laser microsurgery to cut a chromosome tip and monitor it as it moves away from its pole toward its sister partner. Figure demonstrates a chromosome arm that is cut and moves toward its partner. These studies have determined that the tethers are elastic and that the elasticity is dependent on phosphorylation. , Additionally, Forer et al have found that as the tethers elongate and the cell progresses through anaphase, the tethers loose elasticity. , When optical tweezers were used to trap a fragment tip that was created with laser scissors, the force that the tethers imparted on its partner was found to be ∼1.5 pN . The function of the tethers is not completely understood.…”
Section: Laser Microsurgery Combined With Optical Tweezersmentioning
confidence: 99%
“…In this special issue, we highlight two exciting optical trapping applications [9][10] in the area of cell biology.…”
Section: Optical Trapping Applicationsmentioning
confidence: 99%